Primary high-grade serous cancer arising from uterosacral ligament endometriosis: two case reports - Ming Chen; Yuedi Zhang; Manman Xu; Duo Liu; Yang Yang; Shuzhong Yao (Journal of International Medical Research, 2022)
Although high-grade serous cancer (HGSC) accounts for >70% of ovarian epithelial cancers, it is rarely associated with endometriosis. No previous study has reported an association between the malignant transformation of uterine ligament endometriosis and HGSC. Here, we reported two cases of Chinese female patients with HGSC arising from endometriosis in the uterosacral ligament. They had a long-term history of endometriosis and dysmenorrhea. Both were diagnosed with HGSC at stage IIB. They underwent operations and six cycles of chemotherapy with paclitaxel and carboplatin and have remained disease-free to date. Genomic analysis showed no known/suspected pathogenic variations or somatic homologous recombination deficiency in the two cases. In conclusion, these rare cases of HGSC from endometriosis might indicate a new origin of ovarian type II carcinoma. Patients with a long-term history of endometriosis and sudden aggravation of dysmenorrhea or vaginal bleeding should be aware of the possibility of endometriotic malignant transformation.